The Investigation of Association Between Il-10- 1082 Polymorphism and Human Papillomavirus Infection in Prostatic Tissue Samples - Etem, Ebru; Bulut, Yasemin; Akpolat, Nusret; Askin, Yasemin; Elyas, Halit; Yarkin, Fugen (Galenos Yayincilik, 2012)
Introduction: Some studies of prostate cancer (PCa) have reported the presence of human papillomavirus (HPV) DNA. Polymorphisms in IL-10 gene can influence inflammation and immune response and may be related to the risk of prostate cancer. The capacity for IL-10 production varies according to the genetic composition of the IL-10 locus. We aimed to elucidate the relation between HPV infection and IL-10 polymorphism for the development of prostate cancer. We examined 108 formalin-fixed specimens for the existence of HPVs DNA and IL- 10 - 1082 genotype distribution. Materials and Methods: The DNA are extracted from archival prostate tissues of totally 108 patients, 40 of whom with adenocarcinoma and 68 with benign prostatic hyperplasia (BPH). Genotypes of IL- 10 - 1082 single nucleotide polymorphism (SNP) were performed using allele specific polymerase chain reaction (ARMS). HPV detection was performed by using conventional HPV primers. Results: HPVs DNA was detected in 15 of 68 BPH specimens (22%) and in 16 of 40 prostate PCa specimens (40%). Distribution of IL- 10 - 1082 genotype was not statistically different between PCa and BPH using chi-square (p> 0.05). There was not any association between HPVs DNA positivity and IL- 10 - 1082 genotypes. Conclusion: The results suggest that the HPVs DNA positivity might be involved in the etiology of a minority of prostate cancers. As result, we consider that future investigations are needed to provide conclusive evidence on the role of this pathogen and genes in the prostate cancer.
Keywords: Human papillomavirus; prostatic cancer; benign prostatic hyperplasia; interleukin-10; polymorphism